Strategies to Strengthen Vocational Education in Islamic Contexts: Preparing Madrasah Aliyah to Face the Challenges of Industry 4.0 - Saridudin, Saridudin; Rahim, Husni; Rosyada, Dede; Zuhdi, Muhammad; Dahri, Harapandi (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2024)
Many efforts have been made to strengthen vocational education in Madrasah Aliyah, one of which is by implementing skills education. However, this effort has not been running optimally because the right strategy has not been implemented. This study aims to analyze the strategy for strengthening vocational education in Madrasah Aliyah in responding to the challenges of the industrial era 4.0. This study examines how the orientation of the curriculum and school culture develops in Madrasah Aliyah so that they are relevant to the business world and industry and maintain their Islamic existence. This study uses a qualitative phenomenological approach involving two Madrasah Aliyah in West Java: MAN 1 Garut and MAN 3 Tasikmalaya City. Using a purposive sampling technique, the researcher selected two principals, eight vice principals, 15 teachers, and 45 students, each representing each school. The results of the study indicate that the strategy for strengthening vocational education in Madrasah Aliyah is to implement skills education that is linked and matches and is relevant to the demands of the Industrial Revolution 4.0 by considering three aspects, namely the curriculum, school culture-oriented towards Islamic culture, and building partnerships with the Business World and Industry. This study concludes that implementing vocational education by organizing several skills education in Madrasah Aliyah is the right choice in responding to the challenges of Industry 4.0, especially the demands of the world of work. This study recommends the importance of preparing entrepreneurial competencies for Madrasah students so that they are ready to face the challenges of the world of work in the era of the Industrial Revolution 4.0.